Influence of verbal, auditory and visual incentives on art perception and reception of primary school students - Marko Popadić; Siniša Ristić (Биомедицинска истраживања, 2020)
Introduction: Art reception and experiencing is a complex process, containing creative components. The experience of a work of art involves reproduction, in the viewer's consciousness, of the experiences and excitement that the artist himself or herself have undergone in the process of creating the same works of art. When viewing visual images, our perception is directed towards the identification of objects, and when viewing visual images as works of art, we also tend to experience them - we subjectively react to elements, such as stylistic and structural characteristics. The aim of the research is to examine the effectiveness of the experimental program named the Impact of Verbal, Auditory and Visual Incentives, designed to foster students' visual perception and visual reception during art education. Methods: The experimental method with parallel groups was used. The research included the sample consisting of 98 students, out of which 45 belonged to experimental group while 53 were control students from Trebinje region. Test LV1, examining visual creativity, as well as visual perception and visual reception (art appreciation), was used. Results: The results indicated that the experimental program influenced the development of the visual perceptive (F = 3.76; p = 0.05) and visual receptive (F = 8.01; p = 0.00) abilities among students during art education because the experimental group students achieved significantly better results than the control group students. The experimental program was aligned with the curriculum and designed to influence the development of students' visual-perceptual and visual-receptive abilities. Conclusion: The obtained results indicate that it is possible to influence the development of students' visual-perceptual and visual-receptive abilities by using a specially designed program, aimed at stimulating verbal, auditory and visual aspects of visual expression.
Keywords: art perception; art reception; art education